Emerging roles of histone deacetylases in adaptive thermogenesis - Zhou, Ruonan; Cao, Yue; Xiang, Yingying; Fang, Penghua; Shang, Wenbin (Frontiers in Endocrinology, 2023)
Brown and beige adipose tissues regulate body energy expenditure through adaptive thermogenesis, which converts energy into heat by oxidative phosphorylation uncoupling. Although promoting adaptive thermogenesis has been demonstrated to be a prospective strategy for obesity control, there are few methods for increasing adipose tissue thermogenesis in a safe and effective way. Histone deacetylase (HDAC) is a category of epigenetic modifying enzymes that catalyzes deacetylation on both histone and non-histone proteins. Recent studies illustrated that HDACs play an important role in adipose tissue thermogenesis through modulating gene transcription and chromatin structure as well as cellular signals transduction in both deacetylation dependent or independent manners. Given that different classes and subtypes of HDACs show diversity in the mechanisms of adaptive thermogenesis regulation, we systematically summarized the effects of different HDACs on adaptive thermogenesis and their underlying mechanisms in this review. We also emphasized the differences among HDACs in thermogenesis regulation, which will help to find new efficient anti-obesity drugs targeting specific HDAC subtypes.